2020
DOI: 10.1002/jcsm.12588
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of frailty and osteosarcopenia in prematurely aged PolgA(D257A/D257A) mice

Abstract: Background Frailty is a geriatric syndrome characterized by increased susceptibility to adverse health outcomes. One major determinant thereof is the gradual weakening of the musculoskeletal system and the associated osteosarcopenia. To improve our understanding of the underlying pathophysiology and, more importantly, to test potential interventions aimed at counteracting frailty, suitable animal models are needed. Methods To evaluate the relevance of prematurely aged P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Inspired by a previous study, which characterized the bone phenotype and the development of frailty in the PolgA mouse model [41], this study assessed the impact of long-term in vivo micro-CT imaging on hallmarks of osteopenia and frailty in individual mice during the process of aging. The unique study design, for which a large cohort of animals was aged in parallel up to 46 weeks of age, provided the possibility not only for cross-sectional comparisons between genotypes and between imaging groups (i.e., that were scanned at different time-points) but also for longitudinal comparisons within individual animals (i.e., that were scanned both at young adult and old age).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by a previous study, which characterized the bone phenotype and the development of frailty in the PolgA mouse model [41], this study assessed the impact of long-term in vivo micro-CT imaging on hallmarks of osteopenia and frailty in individual mice during the process of aging. The unique study design, for which a large cohort of animals was aged in parallel up to 46 weeks of age, provided the possibility not only for cross-sectional comparisons between genotypes and between imaging groups (i.e., that were scanned at different time-points) but also for longitudinal comparisons within individual animals (i.e., that were scanned both at young adult and old age).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies of cross-sectional [42,43,47] parameters and FI between genotypes was observed both when groups were cross-sectionally compared and when individual mice were monitored over time. Interestingly though, in vivo micro-CT imaging over 20 weeks showed that this difference in bone micro-architecture was not due to bone loss in PolgA mice, but rather in the inability to reach peak bone mass, of which a more comprehensive description has been provided elsewhere [41]. Interestingly, the registration of consecutive micro-CT images revealed that PolgA mice had lower bone remodeling activities compared to WT as shown by reduced bone formation and resorption rates, with no differences in the net remodeling rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of long-term in vivo micro-CT imaging on hallmarks of osteopenia and frailty in aging mice, we coupled longitudinal assessments of the clinical mouse frailty index with an established in vivo micro-CT imaging approach to monitor the changes in static and dynamic bone morphometric parameters of the sixth caudal vertebrae in a mouse model of accelerated aging, specifically the PolgA (D257A/D257A) mouse. Compared to their wild-type littermates (PolgA (+/+) , referred to as WT), PolgA (D257A/D257A) (referred to as PolgA) mice have been shown to develop multiple signs of aging by the age of 40 weeks, whereas no phenotypical differences between genotypes were observed at 20 weeks of age [41][42][43]. Therefore, in this study, female PolgA and WT were monitored between the ages of 20 and 46 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has subsequently been used in middle-aged and aged mice [22]. By combining long-term in vivo micro-CT imaging of the 6 th caudal vertebrae with longitudinal FI measurements, we have recently identified hallmarks of frailty and senile osteoporosis in the PolgA (D257A/D257A) mutator mouse [41], which, due to a defect in the proofreading activity of its mitochondrial DNA polymerase gamma, exhibits a premature aging phenotype [42,43]. In this study, we assessed whether this long-term in vivo micro-CT imaging approach has biasing effects on the local and systemic level at various stages of the aging process, and whether these effects differ between genotypes.…”
Section: Introductionmentioning
confidence: 99%